2014
DOI: 10.1155/2014/962102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Base Metals and Platinum Group Metals in Nitrogen, M Codoped TiO2 (M = Fe, Cu, Pd, Os) for Photocatalytic Removal of an Organic Dye in Water

Abstract: The photocatalytic performance of a number of nonmetal and metal codoped TiO2for the degradation of eosin yellow under simulated solar radiation was investigated. The synthesised materials were characterised by FTIR, Raman spectroscopy, XRD, DRUV-Vis, SEM, and TEM. The N, metal codoped TiO2containing 0.5 wt.% of the metal consisted mainly of the anatase phase, with a particle size range of 15–28 nm. The particles were largely spherical and shifted the absorption edge well into the visible region. Band gap redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…As shown in Figure b, FTIR spectra show several vibrational features with 3500 cm –1 due to surface hydroxyl stretch and broad features below 1000 cm –1 . Such broad features might be due to Ti–O stretches that have vibrational frequencies near 700–900 cm –1 , or broad electronic absorption due to dopants such as oxygen vacancies . Also, since the P25 we are using is a mixture of rutile and anatase, the vibrational frequency could be broad due to the presence of multiple Ti–O species.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure b, FTIR spectra show several vibrational features with 3500 cm –1 due to surface hydroxyl stretch and broad features below 1000 cm –1 . Such broad features might be due to Ti–O stretches that have vibrational frequencies near 700–900 cm –1 , or broad electronic absorption due to dopants such as oxygen vacancies . Also, since the P25 we are using is a mixture of rutile and anatase, the vibrational frequency could be broad due to the presence of multiple Ti–O species.…”
Section: Resultsmentioning
confidence: 99%
“…Kuvarega et al . also reported the effect of metals (Fe, Cu, Pd, Os) on the photocatalytic activity and concluded that the ability of the photocatalyst to degrade the dye depends on the nature and type of metal dopant in the codoped TiO 2 system .…”
Section: Introductionmentioning
confidence: 99%
“…FTIR spectra of the synthesized photocatalysts are given in Figure . The FTIR spectra of TiO 2 and Pt/TiO 2 particles are nearly the same, indicating that Pt impregnation did not affect the physical state of TiO 2 as it was expected. , The broad peak between 500 and 1000 cm –1 is due to the Ti–O and Ti–O–Ti stretching modes. , Peaks at 1630 cm –1 and the wider peak at around 3300 cm –1 were attributed to the H–OH bending and the O–H stretching of the hydroxyl group, respectively. The hydroxyl groups on the surface of P25 and water adsorbed by the surface enhance the photocatalytic water splitting since they prevent the recombination reaction and promote charge transfer by acting as molecular adsorption and hole scavenging sites; the peaks at 1630 and 3300 cm –1 are also apparent in other photocatalysts.…”
Section: Resultsmentioning
confidence: 51%